The influence of human exploration on the microbial community structure and ammonia oxidizing potential of the Su Bentu limestone cave in Sardinia, Italy. - Stefan Leuko; Kaisa Koskinen; Laura Sanna; Ilenia M D'Angeli; Jo De Waele; Paolo Marcia; Christine Moissl-Eichinger; Petra Rettberg (PLoS ONE, 2017)
The bacterial diversity in the Su Bentu Cave in Sardinia was investigated by means of 16S rRNA gene-based analysis. This 15 km long cave, carved in Jurassic limestone, hosts a variety of calcite speleothems, and a long succession of subterranean lakes with mixed granite and carbonate sands. The lower level is occasionally flooded by a rising groundwater level, but with only scarce input of organic remains (leaves and charcoal fragments). On the quiet cave pools there are visible calcite rafts, whereas walls are locally coated with manganese deposits. In the drier upper levels, where organic input is much more subdued, moonmilk-a hydrated calcium-magnesium carbonate speleothem-can be found. Relative humidity approaches 100% and the measured mean annual cave air temperature is 14.8°C. Samples were obtained in 2014 from calcite rafts, moonmilk, manganese oxide deposits and soil (limestone and granite grains). Microclimatic conditions in the cave near the sampling sites, sample properties, physico-chemical parameters of water, and sediment composition were determined. The microbial community of this system is predominately composed of the phyla Proteobacteria, Actinobacteria, Acidobacteria, Nitrospirae, and Firmicutes. Sampling sites near the entrance of the cave and in close proximity of the underground campsite-located 500 meters deep into the cave-revealed the highest diversity as well as the highest number of human associated microorganisms. Two samples obtained in very close proximity of each other near the campsite, indicate that the human impact is localized and is not distributed freely within the system. Analysis of the abundance of bacterial and archaeal amoA genes revealed a far greater abundance of archaeal amoA genes compared to bacterial representatives. The results of this study highlight that human impact is confined to locations that are utilized as campsites and that exploration leaves little microbial trails. Furthermore, we uncovered a highly specialized microbiome, which is perfectly adapted to survive and thrive in an environment with low nutrient availability.